Principles of Unity in Noordin Hassan's "1400" - Md. Yousoff, Rohani (Malay Literature, 2017)
Man's responsibilities extend from himself to the people around him, the community and the environment. This article will identify such responsibilities based on al-Faruqi's principles of unity to further ascertain Islamic elements either through the decisions and actions of the characters featured in the play "1400" by Noordin Hassan, especially through its main character, Dolah. The intention ( niyāh ) of Dolah when he decides and acts based on his weaknesses which include jealousy and greed. But at last Dolah becomes conscious of the error of his ways which then leads him away from evil to goodness, alluding to the story of the holy Prophet's own Hijrah. In "1400" Noordin Hassan delivers the message of Islam as his responsibility and duty as a Muslim, to seek knowledge in order to acquire wisdom for himself and for other Muslims through the gracious manner of theatre. Keywords: principle of unity, responsibilities, 1400, al-Faruqi, Noordin Hassan